Comparison of 3 Different Releasable Suture Techniques in Trabeculectomy. Issue 4 (July 2016) - Duman, Fulya; Faria, Bruno; Rutnin, Nont; Guzel, Huseyin; Ekici, Feyzahan; Waisbourd, Michael; Katz, L. Jay; Moster, Marlene R.; Spaeth, George L.
Purpose: The use of releasable sutures provides an effective and simple way of titrating intraocular pressure (IOP) postoperatively. The purpose of this study was to compare the surgical outcome of 3 releasable suture techniques for closing scleral flaps in patients undergoing primary trabeculectomy. Methods: The Wills Eye Glaucoma Research Center retrospectively reviewed the charts of patients who underwent primary trabeculectomy by 3 surgeons using 3 different releasable suture techniques. Ninety eyes of 90 glaucoma patients were divided into 3 groups by releasable suture technique (n = 30 eyes for each group). Main outcome measures included best-corrected visual acuity (BCVA), intraocular pressure (IOP), rate of surgical success, use of supplemental medical therapy, need for additional glaucoma surgery, and complications during suture removal. Results: The BCVA and IOP were similar among the groups for all follow-up visits. As a determinant of success rate of trabeculectomy, mean decrease of IOP after surgery was over 30% in all groups (p = 0.43). The number of postoperative antiglaucomatous medications, number of complications, and need for an additional glaucoma surgery were similar in all groups (p = 0.40, p = 0.87, and p = 0.47, respectively). The differences in suture-related complications, defined as suture break or need for laser suture lysis, were not significant among the groups (p = 0.09). Conclusions: We found that the 3 most common surgical techniques had similar mechanisms of action. All techniques were safe and effective, yielding similar outcomes. All 3 techniques can be used for closing scleral flaps in patients undergoing primary trabeculectomy.